1998
DOI: 10.1016/s0092-8674(00)81168-x
|View full text |Cite
|
Sign up to set email alerts
|

Jak2 Deficiency Defines an EssentialDevelopmental Checkpoint in DefinitiveHematopoiesis

Abstract: Janus kinases (Jaks) play an important role in signal transduction via cytokine and growth factor receptors. A targeted inactivation of Jak2 was performed. Jak2-/- embryos are anemic and die around day 12.5 postcoitum. Primitive erythrocytes are found, but definitive erythropoiesis is absent. Compared to erythropoietin receptor-deficient mice, the phenotype of Jak2 deficiency is more severe. Fetal liver BFU-E and CFU-E colonies are completely absent. However, multilineage hematopoietic stem cells (CD34low, c-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
515
0
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 762 publications
(532 citation statements)
references
References 73 publications
12
515
0
5
Order By: Relevance
“…There is also good evidence suggesting essential role for Jak2-STAT5 pathway in erythropoiesis in vitro and in vivo (Wakao et al, 1997;Iwatsuki et al, 1997;Parganas et al 1998;Neubauer et al, 1998). Our preliminary experiments, however, indicated that none of the transgenes used in this study (ras12V, ras17N, and MAPKKm) induced signi®cant alterations in the basal or EPO-induced phosphorylation of endogenous Jak2 protein nor did the ras17N gene a ect the DNAbinding activity of endogenous STAT5 protein (our unpublished observation).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…There is also good evidence suggesting essential role for Jak2-STAT5 pathway in erythropoiesis in vitro and in vivo (Wakao et al, 1997;Iwatsuki et al, 1997;Parganas et al 1998;Neubauer et al, 1998). Our preliminary experiments, however, indicated that none of the transgenes used in this study (ras12V, ras17N, and MAPKKm) induced signi®cant alterations in the basal or EPO-induced phosphorylation of endogenous Jak2 protein nor did the ras17N gene a ect the DNAbinding activity of endogenous STAT5 protein (our unpublished observation).…”
Section: Discussionmentioning
confidence: 58%
“…Conversely, forced expression of protein tyrosine phosphatase b2 gene was found to induce di erentiation in murine erythroleukemia cells (Kume et al, 1996). In addition, Jak2-de®cient mice were found to have defects in de®nitive erythropoiesis which lead to embryonic death due to anemia (Parganas et al, 1998;Neubauer et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…JAK-2 mediates signaling via the hematopoietic cytokines EPO, GM-CSF, and thrombopoietin (8,9). Patients receiving the highest dosage of CP-690,550 (30 mg twice daily) had higher incidences of anemia, granulocytopenia, and thrombocytopenia than did the placebo group (12).…”
Section: Discussionmentioning
confidence: 99%
“…Tyk-2 deficiency results in a human primary immunodeficiency similar to the JAK-3 SCID phenotype; however, neither JAK-1-deficient nor JAK-2-deficient humans have been identified, and deficient mice are not viable (8,9). Several of the cytokines that require JAK-1, JAK-2, and/or Tyk-2 activity, including IL-6, IL-12, and IL-23, play a pathogenic role in human rheumatoid arthritis (RA) (10,11), suggesting that inhibiting the JAK family more broadly may be beneficial.…”
mentioning
confidence: 99%
“…Using dominant negative JAK2, we found that JAK2 plays an essential role in activities induced by GM-CSF such as proliferation, induction of immediate early genes, phosphorylation of cellular proteins and bc itself (Watanabe et al, 1996). JAK2 knockout mice are embryonic lethal due to the absence of any de®nitive erythropoiesis (Neubauer et al, 1998;Parganas et al, 1998) and myeloid progenitors from the fetal liver of JAK2-de®cient mice failed to respond to erythropoietin, IL-3 and GM-CSF. When we analysed various bc mutants in BA/F3 and NIH3T3 cells, we found that multiple signaling pathways downstream of JAK2 are activated by hGM-CSFR (Watanabe et al, 1993(Watanabe et al, , 1995.…”
Section: Introductionmentioning
confidence: 99%